Ananas co. production / Petrescu Manja Thomas Kana ... [et.al] - Thomas Kana, Petrescu Manja; Luhat, Gary Leehan (2018)
We are interested to promote agriculture product to another level. We like to supply more good quality of pineapple for any smallholder, businesses and company. We are looking forward to open more branches in Sarawak in order to ease the delivery process. We are looking forward to export our product to oversea. Cover the loses and increase the profit from year to year.